CFTR modulator therapy in patients with cystic fibrosis and an organ transplant. (June 2018) - Mitchell, Ruth M.; Jones, Andrew M.; Barry, Peter J.
Abstract: CFTR modulators are a class of drugs which directly target the defective CFTR protein in cystic fibrosis (CF), improving its function with resultant clinical improvements. Currently these drugs are confined to people with a limited selection of genetic mutations. New modulators are in development which will lead to the majority of patients with CF becoming eligible for treatment. CFTR modulators are currently considered contraindicated in patients with a solid organ transplant. This excludes many patients who may benefit from the multisystem effects of CFTR modulator treatment. In this review, we discuss issues regarding drug interactions, organ transplantation and CFTR modulation.